Punitive Policy Procedures in the Field of Juvenile Delinquency (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstrect The punitive policy in the field of juvenile delinquency is one of the important topics concerned with directing juveniles who have committed acts that conflict with laws or societal ethics. This policy aims to achieve a balance between protecting society from delinquent behaviors and at the same time rehabilitating juvenile delinquents to ensure their integration into society. Properly, it turns out that punitive measures for juveniles are completely different from those directed at adults، Punitive policy in this area is concerned with correcting the behavior of juveniles and motivating them to rebuild their personalities, instead of punishing them with traditional punishments such as imprisonment or imprisonment. Punitive policy focuses on using a number of rehabilitative and educational methods, for example psychological counselling, education, social treatment, and other methods that direct them toward... Positive behaviors، This research aimed to study the various procedures related to the punitive policy that aim to clarify a set of legal foundations and legislative procedures that aim to reform that delinquent person so that he can return to society again after that specific period of punishment, as the punitive policy is considered in the field of delinquency. Juveniles are an important tool to ensure the security and safety of society from deviant behaviors that may threaten the social order ، Dealing with juvenile delinquents effectively reduces the crime rate and limits its impact on society. The descriptive approach has been used, which aims to analyze and describe a specific case or phenomenon by collecting a lot of information and data that is concerned with presenting and analyzing this important topic of procedures related to punitive policy. For the field of juvenile delinquency, in addition to using the comparative approach that aims to clarify many of the differences and differences between some different laws،Here, Iraqi law will be compared with Lebanese law in the research topic to present a number of legal materials concerned with clarifying those punitive procedures between the two laws. The research has been divided into two basic sections, and the first section appears to discuss the investigation and trial of juvenile offenders, next to the second section, which presents the penalties. Confronting juvenile delinquency،The research reached a number of important results that the punitive policy contributes to ensuring the rights of juveniles by taking into account their age and psychological and social conditions, and providing them with the necessary support in accordance with international human rights standards, in addition to reaching a number of important recommendations, including that an alternative punishment policy should be adopted، Such as community work or educational and social programs instead of imprisonment, in order to reduce the impact of imprisonment on the psychology of juveniles and provide an educational environment aimed at improving their behavior. In addition, integrated rehabilitation programs should be developed and implemented that include psychological treatment, social guidance, as well as vocational education for juvenile delinquents, and the goal is to rehabilitate and integrate them. In society positively, and providing them with skills that help them avoid deviant behavior in the future. Keywords: Penal policy, juvenile delinquency, rehabilitation, special courts, legal procedures.